Molecular typing and biological characteristics of Pseudomonas aeruginosa isolated from cystic fibrosis patients in Brazil - Stehling,Eliana Guedes (2010)
The present study had as objective to evaluate the genotypic diversity and biological characteristics, such as hemolysin, protease, elastase of 56 clinical strains of Pseudomonas aeruginosa isolated from 13 cystic fibrosis (CF) patients attending at the School Hospital of Campinas State University (UNICAMP), Brazil. Genotypic diversity has been determined by Ribotyping (RT) and the pattern of the enterobacterial repetitive intergenic consensus PCR (ERIC-PCR) of each strain. The production of elastase was significantly different only among mucoid and nonmucoid isolates. Joint results obtained by (RT) and ERIC-PCR methods were able to discriminate all strains isolated from both the same and different patients. Additionally, we observed four strain clusters with low diversity. The most infective strains were located in just two clusters. These results suggest that either there is a strong selection towards a specific genotype or that specific isolates could be responsible for the initial and subsequent colonization processes. More studies are necessary to know if these conclusions can be generalized for the general CF population